Предмет: Алгебра,
автор: CherchenkoNika
Помогите решить
(X^2-1)^2+(x^2-6x-7)^2=0
Ответы
Автор ответа:
0
a² -b² =(a -b)(a+b)
(x²-1 -(x²-6x-7))(x²-1 +(x²-6x-7)) =0
(x²-1-x²+6x+7)(x²-1+x²-6x-7) =0
(6x +6)(2x² -6x -8) =0
6x +6 =0
6x = -6
x1 = -1
2x² -6x -8 =0
D =36 +4*2*8 =100 =10²
x2 =(6 -10)/4 = -1
x3 =(6 +10)/4 =4(не является корнем уравнения)
ответ: x = -1
(x²-1 -(x²-6x-7))(x²-1 +(x²-6x-7)) =0
(x²-1-x²+6x+7)(x²-1+x²-6x-7) =0
(6x +6)(2x² -6x -8) =0
6x +6 =0
6x = -6
x1 = -1
2x² -6x -8 =0
D =36 +4*2*8 =100 =10²
x2 =(6 -10)/4 = -1
x3 =(6 +10)/4 =4(не является корнем уравнения)
ответ: x = -1
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Русский язык,
автор: davidtroyanov
Предмет: Химия,
автор: HelloItSmeMARI2O
Предмет: Биология,
автор: vika2002roza
Предмет: Алгебра,
автор: Simbacet